SOSIALISASI PEMANFAATAN LIMBAH KULIT DAN KEPALA UDANG MENJADI BERNILAI KOMERSIAL GUNA MENINGKATKAN EKONOMI MASYARAKAT DESA GLUGUR MAKMUR - Dian Ayu Adriani; Zulfa Khairina Batu Bara; Dicky Apdilah; Fahrul Rizal; Irma Yunita; Mutia Mutia; Nur Indah Febriani (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: This activity aims to empower the Glugur Makmur Village community by utilizing and developing shrimp shell and head waste into commercially valuable stock products. Until now, shrimp waste has been considered worthless and often causes environmental pollution. With this innovation in processing into stock, it is hoped that the community will gain new, productive skills and be able to increase family income. Specific targets to be achieved are increasing community knowledge about the importance of hygienic and environmentally friendly shrimp waste management, training the community in techniques for processing shrimp shells and heads into high-quality powdered and liquid stock, equipping the community with simple business management skills, digital marketing, and branding strategies to ensure product acceptance in the market. Implementation methods include outreach and education on the economic potential of shrimp waste, technical training in product processing and packaging, mentoring in small business management, and the implementation of digital-based marketing strategies. Activities will be conducted in a participatory manner, directly involving the community, so that the skills acquired can be applied independently. Through this program, the people of Glugur Makmur Village are expected to be able to produce commercially valuable shrimp broth products, expand business opportunities, and collectively improve economic well-being. Keywords: Utilization, Business Management, Shrimp Waste Abstrak: Kegiatan ini bertujuan untuk memberdayakan masyarakat Desa Glugur Makmur melalui pemanfaatan dan pengembangan limbah kulit serta kepala udang menjadi produk kaldu bernilai komersial. Selama ini, limbah udang hanya dianggap tidak bernilai dan sering menimbulkan pencemaran lingkungan. Dengan adanya inovasi pengolahan menjadi kaldu, diharapkan masyarakat memperoleh keterampilan baru yang produktif serta mampu meningkatkan pendapatan keluarga. Target khusus yang ingin dicapai adalah meningkatkan pengetahuan masyarakat tentang pentingnya pengelolaan limbah udang secara higienis dan ramah lingkungan, melatih masyarakat dalam teknik pengolahan kulit dan kepala udang menjadi kaldu bubuk maupun cair yang berkualitas, membekali masyarakat dengan kemampuan manajemen usaha sederhana, pemasaran digital, serta strategi branding agar produk dapat diterima pasar. Metode pelaksanaan meliputi sosialisasi dan penyuluhan mengenai potensi ekonomi limbah udang, pelatihan teknis pengolahan dan pengemasan produk, pendampingan manajemen usaha kecil, serta penerapan strategi pemasaran berbasis digital. Melalui program ini, masyarakat Desa Glugur Makmur diharapkan mampu menghasilkan produk kaldu udang yang bernilai komersial, memperluas peluang usaha, dan meningkatkan kesejahteraan ekonomi secara kolektif. Kata Kunci : Pemanfaatan,Manajemen Usaha,Limbah Udang